Buckingham Fountain (Arena Photo Post Card Co.)
One of Chicago's seven wonders, it is the largest fountain of its type in the world and cost upward of $1,000,000 to build. It forms the centerpiece of Grant Park, opposite the business section of the city. Set in a landscaped garden 600 feet square, the column of water rises to a height of 90 fett when in full play. The fountain is best seen at night, when five basic colors are reflected through the waters, changing at intervals.